Hygrothermal Behaviour of Three Internal Retrofit Prototype Solutions. (November 2015) - Galliano, R.; Stahl, T.; Brunner, S.; Zhao, S.; Masera, G.; Aliprandi, S.
Abstract: Although the application of internal insulation to existing perimeter walls poses significant challenges in terms of building physics and loss of habitable space, it is sometimes an inevitable choice because of practical or legislative constraints. Innovative solutions are then required to deliver satisfying performances and reduce nuisance to inhabitants of residential buildings in case they are going to remain in their flats during the retrofit works. Three systems for inner thermal retrofitting purposes have been designed and produced as prototypes. Two of them are composed by silica aerogel containing fibrous material: the first one is a rigid flat laminated panel, the second one is a rollable solution with a fabric finishing layer. The third insulating system is a perlite based board with a hydrophobic layer. All the materials composing the retrofit solutions have been characterized by means of laboratory tests in order to measure their main hygrothermal properties. In fact, some parameters are fundamental for determining the hygrothermal performance of the composite systems: thermal conductivity, at dry and wet state (moisture dependant), water vapour diffusion resistance factor, hygroscopic sorption at isotherm condition and water absorption coefficient. All those measured data were necessary for optimizing the solutions, guaranteeing energy efficiency and vapour open layers to systems that are intended for installation on existing walls.